UJI BEBERAPA EKSTRAK TANAMAN TERHADAP JAMUR PATOGEN PADA BENIH PADI (Oryza sativa L.) DAN DAYA KECAMBAH BENIH - Nurul Fatihah; Muhammad Ali; Yunel Venita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Seedborne diseases on rice seeds can be controlled by using plant extracts which applied by seed treatment. The plants used, such as: green betel leaves extract, turmeric rhizome, and ketepeng cina leaves extract. The aim of this research is to study the effect of aplication of several plants extract and obtain the best extract to control fungal pathogenic on rice seeds and the effect to germination rice seeds. The research has been conducted at laboratory plant disease and greenhouse Experimental Field of Faculty of Agriculture, Riau University Pekanbaru. This reseach has been conducted experimentally by using a completely randomized design (CRD) consisting of 4 treatments, namely: without addition plants extract (E0), green betel leaves extract 40% (E1), turmeric rhizome 25% (E2), and ketepeng cina leaves extract 15% (E3). The result showed that the application of ketepeng cina leaves extract could inhibit the growth of Pyricularia sp. 36,50%, Alternaria sp. 76,00% and Drechslera sp. 58,50%, but not contaminated fungi, such as: Rhizopus sp., Aspergillus sp., Mucor sp. and Penicillium sp. The application of the three plants extract were not able to affect seed germination rate, sum of normal seed growth, seedling growth and the decreatesum of symptomatic disease seedlings.